FACTORS WHICH INFLUENCE LIQUID ASSETS IN SHARIA BANKS: A CASE STUDY OF PT BANK SYARIAH MANDIRI 2016-2017 - Taryana Harun (Universitas Muhammadiyah Kendari, 2020)
Banks manage liquidity carefully because of differences in fund tenor collected and channeled. Meanwhile, at the same time, it must fulfill transaction needs, reserve requirement, current liabilities, and be cautious in facing sudden liquidity needs. Therefore, bankshold a sufficient amount of liquid assets. Liquidity management tends to be a trade-off. On one side, insufficient liquid assets can cause banks to be unable to carry out transactions with its customers or fulfill its maturity obligations. On another side, high liquid assets can result in a lost opportunity, because the liquid assets do not provide a return. The purpose of this research is to analyze what factors influence the level of banks liquid assets. This research was conducted using a dual regression model to analyze the variables studied, with a case study of PT Bank Syariah Mandiri from 2016-2017.The dependent variable was the level of liquid assets. Meanwhile, the independent variables were the amount of third party funds, financing growth, financial market access between banks, current liabilities, and previous month profit. The research results reveal that two variables are statistically significant towards bank liquid assets, which are third-party funds and previous month profit. Third-party funds and previous month profit have a positive and significat influence towards liquid assets. Meanwhile, the other variables do not significantly determined liquid assets.